INTERVENSI KONSELING COGNITIVE BEHAVIOR BERBASIS PSIKODRAMA UNTUK MEREDUKSI PERILAKU BULLYING VERBAL SISWA SMP - rohani; Darma Putri, Ramtia; Purnama Sari, Syska (IKIP Siliwangi, 2025)
Verbal bullying behavior in junior high school students is a serious problem because it has a negative impact on the mental health and social development of the victim. Behavior such as teasing, insulting, threatening and degrading verbally is often done by students who have power over weak students. The study aims to test the effectiveness of cognitive behavioral counseling through psychodrama techniques in reducing verbal bullying behavior in junior high school students. The method used is quantitative pre-experimental design type one group pretest-posttest. The research sample was taken using purposive sampling technique as many as 5 students of class VIII.4 SMPN 7 Palembang with a high verbal bullying behavior category. Data were collected using questionnaires and documentation and analyzed using the Wilcoxon signed rank test. The results showed a significant decrease before and after being given treatment from a pretest score of 519 and an average of 103,8 (high category) to a posttest of 186 with an average of 37,2 (low category). Statistical test shows Z count -2,023 with Asymp. Sig value 0,043<0,05 proves that cognitive behavior counseling through psychodrama techniques is effective in reducing verbal bullying behavior of junior high school students. These results can be an intervention strategy in the school environment to create a comfortable and conducive learning atmosphere.